GaN‐based high voltage transistors for efficient power switching. Issue 5 (18th February 2013) - Waltereit, Patrick; Reiner, Richard; Czap, Heiko; Peschel, Detlef; Müller, Stefan; Quay, Rüdiger; Mikulla, Michael; Ambacher, Oliver; Krishna, Sanjay; Plis, Elena
Abstract We present results from GaN‐based high voltage transistors used for power switching applications. The static and dynamic properties of transistors on SiC and Si substrates are determined. Overall, this technology is capable to deliver 1000 V breakdown and 95 A output current as well as a lower product of on‐resistance and gate charge than conventional Si‐based structures. Areas of further improvement in epitaxial growth and device processing are outlined in order to combine these high currents and high voltages in a single device. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)